2016
DOI: 10.1002/ajh.24412
|View full text |Cite
|
Sign up to set email alerts
|

Identifying existing Choosing Wisely recommendations of high relevance and importance to hematology

Abstract: Choosing Wisely (CW) is a medical stewardship initiative led by the American Board of Internal Medicine Foundation in collaboration with professional medical societies in the United States. In an effort to learn from and leverage the work of others, the American Society of Hematology CW Task Force developed a method to identify and prioritize CW recommendations from other medical societies of high relevance and importance to patients with blood disorders and their physicians. All 380 CW recommendations were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…The American Society of Hematology (ASH) has been an active participant in the Choosing Wisely initiative, with campaigns completed in 2013 and 2014 that resulted in 10 hematologic tests and treatments that health care providers should question 2,3 . Furthermore, in 2016, the ASH Choosing Wisely Task Force developed a methodology to identify and prioritize 10 Choosing Wisely recommendations from other medical societies that would be of high relevance and importance to patients with blood disorders and their health care providers 4 . In 2019, ASH and the American Society of Pediatric Hematology/Oncology (ASPHO) formed a joint panel to solicit, evaluate, and select items for a pediatric hematology–focused Choosing Wisely list.…”
Section: Introductionmentioning
confidence: 99%
“…The American Society of Hematology (ASH) has been an active participant in the Choosing Wisely initiative, with campaigns completed in 2013 and 2014 that resulted in 10 hematologic tests and treatments that health care providers should question 2,3 . Furthermore, in 2016, the ASH Choosing Wisely Task Force developed a methodology to identify and prioritize 10 Choosing Wisely recommendations from other medical societies that would be of high relevance and importance to patients with blood disorders and their health care providers 4 . In 2019, ASH and the American Society of Pediatric Hematology/Oncology (ASPHO) formed a joint panel to solicit, evaluate, and select items for a pediatric hematology–focused Choosing Wisely list.…”
Section: Introductionmentioning
confidence: 99%
“…7 The Joint Commission and American Society of Hematology have targeted RBC transfusions as one of the most overused procedures in the US hospitals. 8 Although data and guidelines pertaining to plasma utilization are limited, plasma use historically follows RBC transfusion trends. 4,9,10 By contrast, this study demonstrated a national increase in cryoprecipitate utilization.…”
Section: Resultsmentioning
confidence: 99%
“…There is no evidence to support a strong association between thrombophilia and infertility. Thrombophilia testing in this setting may increase cost, with minimal potential benefit and lead to inappropriate use of anticoagulants with no proven benefit [28,29].…”
Section: Evidence-based Tenets Of Thrombophilia Screeningmentioning
confidence: 99%